Rotating Biological Contactor for Biological Treatment of Poultry Processing Plant Wastewater Using Saccharomyces Cerevisiae - Gashem Najafpour; Punita Nook Naidu; Azlina Harun Kamaruddin (ASEAN Journal of Chemical Engineering, 2002)
Biological treatment using attached growth on a rotating biological contactor(RBC) was implemented for wastewater from poultry industries, which containsa high level of organic compounds due to the slaughtering, rendering of bonesand fats, and plucking processes. The wastewater mostly consists of proteins,blood, fat and feathers. Nutrients available in the wastewater may enhance thegrowth of microorganisms, thus, it allows biological treatment to be usedeffectively. On the other hand, there are problems associated with biologicaltreatment processes such as nutrients promoting algae growth. The controlvariables for the attached growth in RBC were wastewater detention time, effectivesurface for attached growth, disc submerged level in the wastewater basin, shaftrotation for aeration, pH control and supplementary nutrients. The attachedgrowth resulted to high COD refPoval. The best treatment was obtained after 24hours with 29 % disc submergence level. The effective surface area for cellgrowth was 10.7 m2 using 60 discs mounted on a shaft. The microorganismused for the attached microbial growth was Saccharomyces cerevisiae. The shaftwas rotating at 11 rpm. The treatment was improved with the addition of 1 v/vof 0.1 molar sodium hydroxide solution to the wastewater for controlling pH. A91 % COD removal was obtained with RBC operating at optimum conditions,with a DO concentration of 3.98 mg/l.Key words: Rotating biological contactors, Aerobic treatment, Poultry processing wastewater,Saccharomyces cereuisiae,Attached growth.